2014
DOI: 10.1186/2193-1801-3-332
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology, risk factors, and impact on hospital mortality of status epilepticus after subdural hematoma in the United States

Abstract: IntroductionSubdural hematoma (SDH) is a well described risk factor in the development of Status Epilepticus (SE), however the epidemiology of SE after SDH is unknown. In this study, we sought to determine the epidemiology of SE, the prevalence of risk factors, and impact on hospital mortality using a large administrative dataset.MethodsData was derived from the Nationwide Inpatient Sample from 1988 through 2011. We queried the NIS database for patients older than 18 years, with a diagnosis of SDH and SE. Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
(94 reference statements)
4
18
1
Order By: Relevance
“…A large epidemiological study reported major organ dysfunction as an independent predictor of mortality. 1,24 Our results showed that the short-term prognosis (acute phase) in elderly patients depends not on comorbidities but on the severity of aSDH, which is expressed by pupillary abnormalities or unconsciousness. 7 Nonetheless, long-term prognosis (3 months' follow-up) in survivors of aSDH also depends on the cumulating comorbidities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A large epidemiological study reported major organ dysfunction as an independent predictor of mortality. 1,24 Our results showed that the short-term prognosis (acute phase) in elderly patients depends not on comorbidities but on the severity of aSDH, which is expressed by pupillary abnormalities or unconsciousness. 7 Nonetheless, long-term prognosis (3 months' follow-up) in survivors of aSDH also depends on the cumulating comorbidities.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies of TBI in patients over 65 years of age have shown that age and GCS score are independent predictors of an unfavorable outcome. 24,27 Indeed, all patients with severe TBI were dependent in daily living activities 6 months after injury, and the mortality rate was 24 times higher than that in patients with a good GCS score. 27 Similarly, the severity of aSDH, as part of TBI, has been reported to be an independent predictor of poor prognosis in several studies observing a younger cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed increase statistical important in incidence of hospitalizations for SDH, from 13 per 100,000 inhabitants in 1988 to 38 per 100,000 inhabitants in 2011; we observed a concomitant increase in the prevalence of status epilepticus associated with SDH, from 0.5% in 1988 to 0.7% in 2011 [12].…”
mentioning
confidence: 62%
“…11,13,14 The reported incidence of seizures in cSDH varies in between 2% and 42%, and some predictors, such as alcoholism, male sex, low Glasgow Coma Scale (GCS) at admission, previous stroke, and hematoma density, were identified in a smaller number of patients. 24,25 Indeed, there are further questions remaining as to with which prognosis and perspective we should be alerted and treat the patients with cSDH-associated ASz. 9,[14][15][16][17][18][19][20][21][22][23] Furthermore, the significance of status epilepticus (SE) in cSDH, which is associated with even higher morbidity and mortality, is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, concerning that, presumably, most of the studies dealt with acute symptomatic seizures, we observed a similar incidence of ASz/SE of 17%. B, Subgroup analysis of outcome assessed via mRS in patients with acute symptomatic seizure (ASz) and status epilepticus (SE) index of suspicion 24. The authors described the possibility of initial underdiagnosis of SE due to low F I G U R E 2 A, Outcome assessed via modified Rankin scale (mRS) in chronic subdural hematoma with acute symptomatic seizures (ASz/ SE) and no seizure at hospital discharge.…”
mentioning
confidence: 99%